Limbah Botol Plastik Sebagai Serat Dapat Meningkatkan Kuat Tekan Dan Lentur Beton Mutu K175 - (Jurusan Teknik Sipil, Politeknik Negeri Semarang), Sutarno, Mawardi, Yusetyowati (Teknis, 2015)
This paper is a part of the research entitles "Waste Plastic Bottles as Fiber on Concrete Panels forincreasing Compressive Strength and flexibility" The addition of plastic bottlefiber on the concrete wall panel aims to increase the compressive strength and tensile / flexural concrete. With the addition of fiber on concrete can reduce the cracks that may be happened as the result of shrinkage. Plastic as an artificialÂ Â  inorganic chemicals complex from chemical complex material or high levels polymeric materials, basically is a carbon compound (Technology Materials, PEDC, 1987).Â  Have are a kinds of Plastic PE(Poly Etylene)types, i.elow-density polyethylene ( LDPE) and high density polyethylene ( HDPE). These type of plastic generally used to making bottles, which have strong anda weak characteristics. Waste mineral waterÂ  bottles areÂ  usedÂ  in this research. This research used laboratory experiments by making concrete K 175, then added with plastic fiberÂ  in varying amounts of 0%, 2%, 4%, 6%, 8%, and 10%. to Cement weight. Then cubeÂ  Specimen samples use made forÂ  compressive strength test andÂ  beam specimentamplestest is made for bending test. The result is : the highest compresisive strength is by addingÂ  2% fiber to theÂ  cementâs weight isÂ Â  208.2 Kg / Cm2 andthehighestÂ  flexural achievement is by adding 4% fiber to the cementâs weightÂ Â  is 47.97 Kg / Cm2.Keywords: Waste Plastics, Precast Concrete, Concrete Fiber